COGNITIVE DECLINE AMONG PATIENTS WITH HYPERTENSION AND ASSOCIATED SOCIO-DEMOGRAPHIC FACTORS - Usama Bin Zubair (Army Medical College Rawalpindi, 2021)
Objective: To determine the frequency of cognitive decline among the patients of hypertension and analyze the associated socio demographic factors.